NEMATODE DIVERSITY IN A RANGE OF LAND USE TYPES IN JAMBI BENCHMARK INDONESIA - I Gede Swibawa & Titik Nur Aeny . (Universitas Lampung, 2010)
Nematode Diversity in a Range of Land Use Types in Jambi Benchmark Indonesia. This study was conducted in Jambi Benchmark, Indonesia from May 2004 to March 2005. Out of 70 sampling points, 35 soil cores were taken from five land use types including forest less intensive, forest intensive, shrub, tree-based intensive, and crop-based less intensive. From each soil core, 300 ml of soil was extracted by flotation and centrifugation technique using sucrose solution. One hundred randomly picked nematodes from each sample were identified to genus level. The collected data were nematode abundance, number of genera, and trophic groups. The results showed that a total of 100 nematode genera within 31 families and 8 orders were found from soil samples of Jambi Benchmark. The abundance of total nematodes, bacterial feeding, and plant feeding nematodes were low in the intensive land use but high in less intensive land uses, i.e. shrub, intensive forest, and less intensive forest. There was no significant correlation between land use intensity and the diversity of nematode taxa. Nematode maturity indices were not sensitive enough to measure ecosystem disturbance caused by human intervention in Jambi Benchmark.